Option A: The rate of change of Function R is less than the rate of change of Function S because [tex]\frac{2}{3}<3[/tex] is true.
Explanation:
The function [tex]S=3x-1[/tex]
The equation for function R can be determined using the slope formula,
[tex]y=mx+b[/tex]
The y-intercept is the value of y, when x = 0.
Thus, the y-intercept is [tex]b=1[/tex].
To determine the slope, let us substitute the coordinates [tex](0,1)[/tex] and [tex](3,3)[/tex].
Because, the points on the straight line have the same slope.
Thus, we have,
[tex]m=\frac{y_2-y_1}{x_2-x_1} \\m=\frac{3-1}{3-0} \\m=\frac{2}{3}[/tex]
Thus, [tex]m=\frac{2}{3}[/tex] and [tex]b=1[/tex]
Let us substitute these values in the formula [tex]y=mx+b[/tex], we get,
[tex]y=\frac{2}{3} x+1[/tex]
Hence, the equation of R is [tex]y=\frac{2}{3} x+1[/tex]
The equation of S is [tex]y=3x-1[/tex]
Comparing the slope of these two equations, we have,
[tex]\frac{2}{3}<3[/tex]
This means that the slope of R is less than the slope of S.
Hence, The rate of change of Function R is less than the rate of change of Function S because [tex]\frac{2}{3}<3[/tex]
Thus, Option A is true.